The effect of Raphanus sativus and Pachyrhizus erosus juice combination on the ethanol-induced gastric of mice - Reza Pertiwi; Aanisah Hanuun; Noval Kurniawati; Petri Siti Khodijah; Dian Fita Lestari; Dyah Fitriani; Doni Notriawan (Universitas Ahmad Dahlan, 2021)
Gastric ulcers can be caused by active inflammation due to impaired mucosal integrity, which causes local or widespread lesions. Gastric ulcers can occur due to the use of ethanol, which has a local effect on the gastric. Therefore, the continuous consumption of ethanol can damage gastric cells. Raphanus sativus and Pachyrhizus erosus contain flavonoids, which are well-known to reduce stomach acid as a curative agent. The objective of this study is to see the effect of Raphanus sativus and Pachyrhizus erosus juice as a preventive agent on alcohol-induced gastric ulcers in mice (Mus musculus). A combination of Raphanus sativus and Pachyrhizus erosus was given at a dose of 100, 300, and 600 mg/kgBW. Specifically, Raphanus sativus was given at a dose of 300 mg/kgBW, Pachyrhizus erosus at a dose of 300 mg/kgBW, and positive control was included using sucralfate. The treatment was carried out for 12 days, and 1 hour after the last day of treatment, 20 ml/kgBW of ethanol induction was given 24 hours after the animals were dissected. The results showed that the index value of gastric ulcers in the normal group, negative control, and the combination of Raphanus sativus and Pachyrhizus erosus juice given orally at a dose of 100, 300, and 600 mg/kgBW (Raphanus sativus at a dose of 300 mg/kgBW, Pachyrhizus erosus at a dose of 300 mg/kgBW, and sucralfate as positive control) were 0; 4.00; 1.00; 1.33; 2.33; 2.67; 0 and 2.00. The results of the histopathological analysis also showed improvement in the gastric of mice fed with Pachyrhizus erosus juice. Therefore, it is inferred that treatment using Raphanus sativus and Pachyrhizus erosus juice can reduce the number of ulcers, increase ratio protection, and repair the cells in gastric histopathology. Additionally, giving a single dose of Pachyrhizus erosus juice results in a more significant gastric improvement.